English-medium instruction and learning difficulties in economics courses among malay students / Norliwa Ab Halim and Roslilee Ab Halim - Ab Halim, Norliwa; Ab Halim, Roslilee (2013)
English language is used globally nowadays. In order to prepare students to venture into this global world and be part of the growing society, students are exposed to the language where most universities are using English as a medium of instruction in lectures or tutorials. Therefore, for students to be able to learn in English they have to understand the language in the first place. For most Malay students whose mother tongue is not English, the level of English proficiency might influence their capability in comprehending the courses taught. A very minimal ability in English would lead to learning difficulties. This will definitely disturb the learning process. As Economics is one of the courses learnt in English in UiTM Pahang, researchers aim to investigate the learning difficulties faced by the Malay students in comprehending the subject with English as the medium of instruction. 100 questionnaires were distributed among Economics students. The selection of sample was based on simple random technique. The findings showed that the overall degree of students' comprehension is not high and that the comprehension level will improve if the lecturers re-explain in their mother tongue language which is Malay (M=4.14). About half of the respondents were found to respond that the difficulties in understanding Economics were due to either solely to the difficulty they had with English language or at least part of the difficulty was due to English.